Análise do sistema de gestão ambiental baseado na norma ISO 14001 no continente americano - Neves, Fábio De Oliveira (2015)
The American Continent is in an extensive industrial and economic development, especially the strengthening of South American countries. Brazil, for example, currently occupies the sixth place in the world economy, in addition of being the tenth country in the world in industrial production, even in the same continent of The United States, which has the largest world economy and increased industrial production. Much of this economic and industrial development often brings up a serious problem that is the emission of pollutants from industry, considering that Brazil emits about 2.7 million tons of dangerous industrial waste, according to data from the Environmental Guide Brazil-Germany. Thus, this study has as its main aim to check which economic, environmental and cultural factors that influence on ISO 14001 certification in the American Continent. Thus, initially presented the characteristics of the ISO 14001 certificate emissions in continents and in major countries that issued the standard. Sooner, tests were done to check which economic, environmental and cultural factors that influence the amount of ISO 14001 certificates issued in the American Continent by multiple regression models adjustment. The data were collected in the ISO Survey, World Bank, United Nations Development Programme and International Energy Agency. The R software was used as a tool for adjusting the multiple regression models. Among the countries of that continent, 13 were analyzed and only two did not show the economic factors as the influence factor in the multiple regression models adjusted with Brazil and the USA. In these models, all presented environmental factors as influencing factors. Only in Brazil the index HDI presented as cultural factor in multiple regression model adjusted. The economic factors: Gross Domestic Product and exports of goods and services and environmental: Carbon Doxide (CO2) and fossil fuel consumption were the most influential in ISO 14001 certification. Venezuela, Uruguay, Colombia and the United States were countries that had factors dependent on each other, featuring the environmental marketing. Briefly, this study brings up several implications: to the gym, new concepts and guidance on the factors that assist in ISO 14001 certification in the American Continent, for the industry and the factors serve as efficiency parameters for the implementation of ISO 14001 standard, and for the Government to improve through factors that do not fit in multiple regression models.